Homework practices and effectiveness: research among the pre and young adolescent children attending three private schools in Kathmandu - Poudyal, Bibek Sharma (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Science in Early Child Development, 2023.